High‐resolution anal manometry: Repeatability, validation, and comparison with conventional manometry. Issue 6 (15th May 2019) - Gosling, Jonathan; Plumb, Andrew; Taylor, Stuart A.; Cohen, Richard; Emmanuel, Anton V.
Abstract: Background: Accurate measurement of anal sphincter function is potentially of value in defining treatment of common pelvic floor disorders. The aim of this study was to establish repeatability and validate high‐resolution anorectal manometry (HRAM) by comparison to conventional manometry (CM). Arising from this work would be definitive normal range data. Methods: Eighty healthy volunteers (40 female) underwent a test‐retest repeatability study. A 16‐channel water‐perfused HRAM catheter was compared to an 8‐channel conventional catheter using a station pull‐through technique. Key Results: High‐resolution anorectal manometry had similar precision to conventional manometry when measuring resting pressure (intraclass correlation coefficient [ICC] 0.73 vs 0.68, HRAM vs CM) and squeeze increment (ICC 0.90 vs 0.94, HRAM vs CM). HRAM measured resting pressures 10% lower than CM and squeeze pressure 27% higher than CM. Conclusions and Inferences: High‐resolution anorectal manometry is a valid technique with comparable precision to CM. HRAM measurements differ considerably to CM, and a new set of normal values must be used. Abstract : A test‐retest repeatability study was performed on 80 healthy volunteers comparing the repeatability of high‐resolution anal manometry (HRAM) with conventional station pull‐through manometry (CM). We found HRAM to be a valid technique with comparable repeatability to CM. HRAM measurements differ considerably to CM, and a new set of normal values must be used.